Nitration of Liquid Natural Rubber by Concentrated Nitric Acid in the Presence of Acetic Anhydride - Doan, Khai Minh; Tran, Trung Bao; Nguyen, Tuan Duy; Ly, Vuong Quoc (Indonesian Journal of Chemistry, 2026)
Liquid natural rubber (LNR) is commonly used as a binder in energetic composites. One of the key areas of interest is the development of energetic polymers to enhance adhesion efficiency and energy. In this study, an energetic liquid polymer—nitrated liquid natural rubber (N-LNR)—was successfully synthesized via nitration of LNR using concentrated nitric acid (HNO3) in the presence of acetic anhydride (Ac2O) and dichloromethane as solvent. The effects of key parameters, including the HNO3/LNR ratio and reaction time, on the degree of nitration and reaction yield were systematically investigated. The degree of nitration was found to increase linearly with the HNO3/LNR ratio, ranging from 7.97% to 32.9%, with a maximum yield of 76.1%. The optimal reaction conditions were identified as an Ac2O/HNO3 molar ratio of 2:1, a reaction time of 1.75 h, and a temperature of 20 °C. Structural analyses by FTIR, 1H-NMR, and 13C-NMR confirmed the presence of cis-1,4-isoprene chains partially substituted with –NO2 and –ONO2 groups, verifying successful nitration at the C=C bonds. These results demonstrated a controllable and efficient method for preparing energetic LNR-based polymers with potential application as binders in propellants and plastic explosives.